(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: Soft Tissue Sarcomas are rare mesenchymal tumors with many subtypes. Clean margin wide resection is recommended for treatment.In this study, the location, histopathological features, clinical and demographic features, recurrence and prognosis of retroperitoneal sarcomas were investigated. Methods: The demographic, histopathological and immunohistochemical data of 18 patients who were operated on with the diagnosis of retroperitoneal mass between March 2016 and June 2021 were evaluated retrospectively. Results: 18 patients were included in the study. 10 patients were male and 8 patients were female. The mean age was 57 (23-81), the median age was 55. While 14 patients were primary sarcoma, 4 patients were recurrent sarcoma. The most common complaint was abdominal pain with 38,87%. The average follow-up time was 26 (0-55) months. The postoperative mean hospitalstay was 5,83 (2-8) days. The average size of the tumor was 19,81 (6,5-36) cm. A total of 8 different histopathological sarcoma types were detected. The most common histology was Dedifferentiated Liposarcoma (44,45%). R0 resection in 10 patients, R1 resection in 6 patients and R2 resection in 2 patient were performed. Organ resection was performed in 6 patients due to organ invasion. During follow-up, 10 patients had a local recurrence and underwent reresection and 6 patients died. The 30-day mortality number was 0. The mean time to detect relapse was 9,3 (1-55) months. Metastasis developed in 2 (11, 11%) patients. Conclusion:Although we are a low-volume hospital for retroperitoneal sarcomas, our results are similar to those in the literature. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 829-835